2019
DOI: 10.31083/j.rcm.2019.04.548
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cardiovascular risk in chronic kidney disease patients: the real silent killer

Abstract: This is an open access article under the CC BY-NC 4.0 license (https://creativecommons.org/licenses/by-nc/4.0/). Chronic kidney disease is a growing public health problem, as its prevalence and incidence have almost doubled over the last three decades. Chronic kidney disease is defined as the presence of an estimated glomerular filtration rate < 60 ml/min/1.73 m 2 and/or proteinuria ≥ 0.150 g/24 h. It has been demonstrated that both proteinuria and reduction in estimated glomerular filtration rate can predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 173 publications
0
46
0
1
Order By: Relevance
“…In addition, more than 30% of patients developed AKI or died during follow-up. It has been widely demonstrated that cardiovascular disease is strictly linked to kidney impairment, since an acute or chronic disorder in one organ may induce an acute or chronic disorder in another one [ 25 , 26 ]. The presence of cardiac dysfunction leads to the activation of the renin-angiotensin-aldosterone-system (RAAS), sympathetic nervous system and vasopressin secretion, leading to fluid retention [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more than 30% of patients developed AKI or died during follow-up. It has been widely demonstrated that cardiovascular disease is strictly linked to kidney impairment, since an acute or chronic disorder in one organ may induce an acute or chronic disorder in another one [ 25 , 26 ]. The presence of cardiac dysfunction leads to the activation of the renin-angiotensin-aldosterone-system (RAAS), sympathetic nervous system and vasopressin secretion, leading to fluid retention [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of HFpEF was challenging and required assessment of clinical history, physical examination, natriuretic peptide testing, echocardiography data, and invasive exercise testing (21). Recently, the Heart Failure Association (HFA) of the European Society of Cardiology (ESC) produced an updated consensus recommendation-the HFA-PEFF diagnostic algorithm including clinical assessments (HF symptoms and signs), diagnostic laboratory tests (including NT-proBNP values), and standard echocardiography (22). Notably, a combination of echocardiographic measurements of cardiac structure and function and BNP levels were recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Kidney Disease is defined as the presence, for at least 3 months, of abnormalities across the urinary system and/or out-of-range levels of two kidney measures, namely, estimated Glomerular Filtration Rate (eGFR) and proteinuria [10]. It has been shown that both low eGFR and high proteinuria levels forecast cardiovascular events, including peripheral vascular disease [11,12]. More specifically, both the two kidney measures, eGFR and proteinuria, have been independently associated with an increased risk for incident abdominal AA as well as with an increase in diameter of the abdominal aorta [9].…”
Section: Introductionmentioning
confidence: 99%